Social Integration and Development of Boy Child in Kenya (London Journal of Medical and Health Research, 2024)
Over the years, so much emphasis has been placed on raising girls to higher levels that society has forgotten about the boy child. At the time, society in Africa and particularly in Kenya was content with the boy child's position and unconsciously focused on the girl child to the alienation of the boy. The callous disregard for boys has caused a decline in their development and performance and caused an identity crisis. Consequently, a significant majority of the African boychild have grown into dysfunctional adults. The main objective of this research was to evaluate the role of social integration on the development of boy child in Kenya. The study used an explanatory research design. The target population unit of analysis was all the 3,500,000 students, 113,200 teachers, 10,463 principals, 3,400,000 parents, 14 heads of mental health hospitals, 129 heads of prisons, and 47 county education officers respectively in Kenya. Stratified-Systematic sampling and purposive sampling were used to identify a sample size of 1,682 respondents selected using the Krejcie and Morgan Table formula. The findings revealed a statistically significant positive moderate correlations between responsibilities (r= 0.11, p
Keywords: Social integration; responsibilities; relationships and mentorship